2020
DOI: 10.21203/rs.3.rs-24620/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of coagulation function by rotation thromboelastometry in critically ill patients with severe COVID-19 pneumonia

Abstract: Critically ill patients with COVID-19 pneumonia suffered both high thrombotic and bleeding risk. The effect of SARS-CoV-2 on coagulation and fibrinolysis is not well known. We conducted a retrospective study of critically ill patients admitted to an intensive care unit (ICU) a cause of severe COVID-19 pneumonia and we evaluated coagulation function using rotational thromboelastometry (ROTEM) on day of admission (T0) and 5 (T5) and 10 (T10) days after admission to ICU. Coagulation standard parameters were also … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0
8

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 11 publications
5
54
0
8
Order By: Relevance
“…Following screening of each title and abstract, a total of 34 potentially eligible articles were considered for inclusion and the full articles were retrieved. Ultimately, 10 articles met the eligibility criteria [28][29][30][31][32][33][34][35][36][37]. There was no disagreement about any of the articles selected for final inclusion in the systematic review.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 4 more Smart Citations
“…Following screening of each title and abstract, a total of 34 potentially eligible articles were considered for inclusion and the full articles were retrieved. Ultimately, 10 articles met the eligibility criteria [28][29][30][31][32][33][34][35][36][37]. There was no disagreement about any of the articles selected for final inclusion in the systematic review.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A total of 10 studies [28][29][30][31][32][33][34][35][36][37] with 389 COVID-19 patients were included in the final systematic review. Nine articles were published after peer review [28][29][30][31][32][33][34][35][36] and 1 article [37] was pre-print. Two studies [36,37] reported prospectively collected data and 8 studies [28][29][30][31][32][33][34][35] reported retrospective data.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations